2016
DOI: 10.1177/1533034615624583
|View full text |Cite
|
Sign up to set email alerts
|

Norcantharidin Inhibits SK-N-SH Neuroblastoma Cell Growth by Induction of Autophagy and Apoptosis

Abstract: Norcantharidin, a low-toxic analog of the active anticancer compound cantharidin in Mylabris, can inhibit proliferation and induce apoptosis of multiple types of cancer cells. However, the anticancer activities of norcantharidin with respect to neuroblastoma, and its underlying mechanisms, have not been investigated. Therefore, our study was designed to determine the efficacy of norcantharidin on SK-N-SH neuroblastoma cell death and to elucidate detailed mechanisms of activity. In the present study, norcanthar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 49 publications
2
13
1
Order By: Relevance
“…certain studies have reported that cantharidin attenuates tumor cell propagation and induction of autophagy (31)(32)(33)(34). Autophagy has been widely investigated in response to various stimuli, including particular anticancer agents (35).…”
Section: Discussionmentioning
confidence: 99%
“…certain studies have reported that cantharidin attenuates tumor cell propagation and induction of autophagy (31)(32)(33)(34). Autophagy has been widely investigated in response to various stimuli, including particular anticancer agents (35).…”
Section: Discussionmentioning
confidence: 99%
“…NCTD, the demethyl-. NCTD, the demethyl-the demethylated form of cantharidin, has exhibited anticancer potential in multiple cancer cell types (8,12,13). However, to the best of our knowledge, the ability of NCTD to suppress the growth of human osteosarcoma cells and the possible underlying mecha-osteosarcoma cells and the possible underlying mecha-and the possible underlying mechanisms have never been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…SK-N-SH cells were purchased from the Cell Resource Center, Shanghai Institutes for Biological Sciences, Chinese Academy of Sciences (Shanghai, China). Dulbecco's modified eagle medium (DMEM, 12100-46; Thermo Fisher Scientific, MA, USA) containing 10% fetal bovine serum was cultured in an incubator at 37°C with 5% CO 2 20 – 22 . The specification of carboplatin injection is 10 mL:100 mg (Qilu Pharmaceutical Co., Ltd, Jinan City, Shandong Province; batch no.…”
Section: Methodsmentioning
confidence: 99%